The administrative and social policy of the Romans in Egypt during the first and second centuries AD - Abdul Kadim Jawad, Maytham (Journal of College of Education, 2022)
Research Summary The Romans did not look at Egypt after they eliminated its rulers from the Ptolemies and annexed it to the Roman settlement, just a state like the rest of the states. A power for any ruler who aspires to be independent from the imperial power in Rome, as it was the main granary of fetters for Rome, and therefore the one who gained independence from it was able to control to a large extent the daily sustenance of the inhabitants of the imperial capital, Rome, and to realize the Emperor Octavius ​​Augustus (27 BC). -14 AD) for this importance, he was keen to ensure its safety, so he placed it under his direct supervision, and no Roman was allowed to visit it except by order of the emperor himself. It has a special entity, as it is the main outlet for Egypt and its wheat, and since the Ptolemaic era it has been a multi-ethnic city as it included elements of several nationalities, including Greek, Roman, Ethiopian, Persian and Arab On the side of the Jew and the Egyptian, and each of these races has its own conditions, constitutional limitations, rights and duties different from the other, and that is why they called it Alexandria, which is next to Egypt. According to its position in that class hierarchy, and this is what we will explain in the folds of this research.